Pycnogonids from marine docks located along the west coast of the Gulf of California, Mexico - de León-Espinosa, Angel; de León-Gonzalez, Jesus Angel; Gómez-Gutiérrez, Jaime (Zootaxa, 2021)
Sea spiders (Class Pycnogonida Latreille, 1810) are chelicerate arthropods, with an extraordinarily reduced body armed with eight to twelve elongated legs. A literature review of taxonomic and ecological studies of pycnogonids from Mexico identified 49 nominal species (~3.6% out of 1,335 species described worldwide). This low species richness is likely caused by limited taxonomic research and intermittent sampling and research efforts initially carried out by foreign scientists (1893–1996) and later by Mexican scientists. The present study investigates the latitudinal gradient of species richness of the pycnogonids associated with nine marine docks located between Cabo San Lucas (22°53’N) and Santa Rosalía (26°58’N) along the west coast of the Gulf of California, 22°53’N Mexico and provides a detailed morphological re-description of each nominal species using light and scanning electron microscopy. Nine nominal pycnogonid species and one unidentified species in the genus Tanystylum were collected and identified from the biological samples collected between 2011–2017. The highest pycnogonid species richness was recorded at Bahía de La Paz (seven species, 24°14’N) and the lowest species richness at Cabo San Lucas (one species) without an evident latitudinal species richness gradient. Anoplodactylus californicus Hall, 1912 and Ammothella spinifera Cole, 1904 were the most abundant species (52% of the total number of individuals). Tanystylum occidentale (Cole, 1904) and Nymphon apheles Child, 1979 were new geographical records for Mexico and Ammothella symbia Child, 1979 and A. californicus were new records for Baja California Sur state. Adding these new geographical records of pycnogonids increased the species richness previously recorded at Baja California Sur from 20 to 24 nominal species and for Mexico, the species richness increased from 49 to 51 nominal species.